Activation of aryl hydrocarbon receptor by 6‐formylindolo[3, 2‐b]carbazole alleviated acute kidney injury by repressing inflammation and apoptosis. Issue 2 (6th December 2020) - Tao, Sibei; Guo, Fan; Ren, Qian; Liu, Jing; Wei, Tiantian; Li, Lingzhi; Ma, Liang; Fu, Ping
Abstract: Acute kidney injury (AKI) is a multifactorial disease of various aetiologies. Aryl hydrocarbon receptor (AhR) is a ligand‐activated transcription factor that responds to ligands to induce or repress gene expressions, thereby regulating a diverse spectrum of biological or pathophysiologic effects. However, the effect of AhR on AKI remains unknown. A single intraperitoneal injection of 50% glycerol was performed to induce rhabdomyolysis in C57BL/6J mice. The bilateral renal pedicles were occluded for 30 minutes and then removed to stimulate renal I/R injury. 6‐formylindolo[3, 2‐b]carbazole (FICZ), a photo‐oxidation product of tryptophan with a high affinity for AhR, was used. The in vitro study was performed on HK‐2 cells. Ferrous myoglobin and FICZ was dissolved in the medium in different cell groups. Treatment with AhR agonist FICZ significantly alleviated the elevation of serum creatinine and urea in AKI. AKI modelling‐induced renal damage was attenuated by FICZ. AhR mainly expressed in proximal tubular cells and could be activated by FICZ administration. Meanwhile, AKI triggered the production of pro‐inflammatory cytokines in injured kidneys, while FICZ inhibited their expressions. Furthermore, FICZ effectively reversed cell apoptosis in AKI models. Mechanistically, AKI stimulated the activation of NF‐κB and JNK pathways in the kidneys, while FICZ significantly suppressed these corresponding protein expressions. For the in vitro study, FICZ also inhibited inflammation and apoptosis in myoglobin or H/R‐stimulated HK‐2 cells. In summary, agonism of AhR by FICZ alleviated rhabdomyolysis and I/R‐induced AKI. FICZ inhibited inflammation and apoptosis via suppressing NF‐κB and JNK pathways in proximal tubular cells.